FORMATION OF DIALOGUE SKILLS OF STUDENTS FROM INVOLVING THEM IN ACTIVE EDUCATIONAL DIALOGUE (Pedagogy of Higher and Secondary Education, 2002)
The verified method of the students' inclusion into active dialogue providing the efficiency of dialogue skillsdevelopment is suggested.